Determinants of caregiver burden in community-dwelling caregivers of patients with severe and persistent mental illness - Mulud, Zamzaliza Abdul; Goodwin, John; Mohamad, Norfidah; Wahab, Patimah Abdul (Intelektual Pustaka Media Utama, 2025)
Loss of independence due to cognitive and functional ability is the main challenge experienced by individuals with severe mental illness. This study aimed to investigate the associated factors of caregiver burden among caregivers of individuals with severe and persistent mental illness living in the community. We used a cross-sectional design with open-ended questions to determine the contributing factors to caregiver burden. A self-administered questionnaire was used to measure caregiver burden and resilience (n=201). Caregiver burden and resilience were operationalized using the caregiver burden inventory scale (CBI) and Connor-Davidson resilience scale (CD-RS), respectively. The findings showed that the caregivers were experiencing a moderate level of caregiver burden (M=30.7, SD=20.3). Caregiving-related stressors are the most important predictor of caregiver burden, explaining 28.3% of the variance in caregiver burden. Finally, the hierarchical analysis found that resilience, caregiver-related stressors, and socio-demographic factors contributed to 52.4% of the variance in caregiver burden. New factors that contributed to the burden, such as lack of support and knowledge deficit, emerged from the qualitative findings. The results highlighted the growing evidence of the role of caregivers' socio-demographic variables, caregiving-related stressors, and resilience to caregiver burden.